The Accounting Impact of IOT Technology on Supporting Innovation for Supply Chains and Logistics in Kingdom of Saudi Arabia: Analytical theoretical study (International Journal of Financial, Administrative and Economic Sciences, 2025)
The world is witnessing a rapid digital transformation in which (IOT) plays a pivotal role in reshaping supply chains and logistics services, contributing to increased operational efficiency and creating new opportunities for innovation. In Saudi Arabia, this technology is seen as a strategic tool to support digital transformation and enhance the competitiveness of economic sectors, aligning with the goals of Vision 2030.This analytical study aims to explore the impacts of (IOT) on supply chain and logistics management, highlighting how the use of smart sensors, real-time tracking, and predictive analytic can improve process flow, reduce costs, and enhance the accuracy of operational decisions. The study also addresses the accounting and financial challenges associated with adopting this technology, including high initial costs, difficulties in reconciling accounts, and managing financial risks linked to technological investments. Additionally, the study examines the regulatory and operational aspects, emphasizing the need for strong governance frameworks to ensure data protection and legal compliance.Through a comprehensive review of research literature and specialized studies, the study provides an in-depth evaluation of the role of (IOT) in improving the performance of supply chains and logistics services in Saudi Arabia. The results highlight the importance of well-planned investments, institutional support, and capacity building to maximize the benefits of this technology, enhancing the efficiency and sustainability of logistics operations and supply chains in an evolving economic environment.
Keywords: The Internet of Things; Accounting Performance; Supply Chains; Logistics; Sustainable Innovation; Sustainable Cost Management; Sustainable Digital Transformation